VOLLEYBALL: METHODOLOGICAL POSSIBILITIES FOR LABOUR ORGANIZATION OF PROFESSIONAL PHYSICAL EDUCATION IN THE SCHOOL ENVIRONMENT (Fiep Bulletin - online, 2016)
This paper seeks to explore the methodological possibilities volleyball at school. Once the mode has been growing increasingly, in view of the volleyball in Brazil has a level of excellence. So the school environment is also preferred for the development of the sport due to the strong influence of sport in the school curriculum of Physical Education locus. But how is the work being developed with the sport at school? What teaching methodologies Volleyball per hour if they have? What would be the most appropriate methodology to work in a school setting? Thus this work aims to seek answers regarding what methodologies outlined for teaching volleyball at school, while pointing out, in our view, what are the, best for a better utilization of the modality in school. To do so we performed a literature search of character / exploration based on the characteristics of the job and it was realized in the clash of the methodologies presented that there is not a more appropriate methodology and what they would approach the ideal would be a combination of various forms of work to achieve a goal of student learning.
Keywords: volleyball; school; methodology.